BEST PRACTICES IN NEW PRODUCT DEVELOPMENT: THE ZYRAY WIRELESS CASE STUDY - P. Koekemoer; A.J. Buys (South African Journal of Industrial Engineering, 2012)
ENGLISH ABSTRACT: Successful high-tech start-up companies are rare. This case study investigates the New Product Development (NPD) process of Zyray Wireless, a very successful startup 3G technology company that originated in South Africa but relocated to California in the USA. The research looked into the differences between generally accepted NPD best practices and those implemented by this start-up company. Zyray Wireless scored above the industry average in the following categories: customer involvement, project selection, product strategy, technological leadership, and product goal. The best practices for metrics, human resource development, documentation, and change control implemented by Zyray Wireless scored at or below the industry average. The best practice results showed that this very successful start-up company focused more on strategy and engineering and less on process control than average. AFRIKAANSE OPSOMMING: Suksesvolle nuwe hoë-tegnologie maatskappye is skaars. Hierdie gevallestudie het die Nuwe Produk Ontwikkelingproses (NPO) ondersoek van Zyray Wireless, ŉ baie suksesvolle nuwe maatskappy wat in Suid-Afrika ontstaan het maar na Kalifornië in die VSA verskuif is. Die navorsing het na die verskille gekyk tussen algemeen aanvaarde NPO beste praktyke en dié wat deur hierdie maatskappy geïmplementeer is. Zyray Wireless het bo die industriegemiddelde gepresteer in die volgende kategorieë: kliëntbetrokkenheid, projekkeuse, produkstrategie, tegnologiese leierskap, en produkdoelwitte. Die beste praktyke vir maatstawwe, menslike hulpbronontwikkeling, dokumentasie, en veranderingsbeheer wat deur Zyray Wireless geïmplementeer is, het onder die industriegemiddeldes gepresteer. Die beste praktykresultate het getoon dat hierdie baie suksesvolle nuwe maatskappy meer gefokus het op strategie en ingenieurswese en minder op prosesbeheer as die gemiddelde.